The apparelling of truth : literature and literary culture in the reign of James VI : a festschrift for Roderick J. Lyall - McGinley, Kevin J.; Royan, Nicola; Lyall, R. J. (Cambridge Scholars, 2010)
Prepared to honour the work of R.J. Lyall, this collection of essays offers new perspectives on the literature and culture of the reign of James VI, from his accession as an infant to the throne of Scotland, through the Union of the Crowns, to his final.